Association of nutritional status with urinary iodine deficiency in Brazilian pregant women - Thaís Cristina Serra da Silva; Poliana Cristina de Almeida Fonseca Viola; Ana Karina Teixeira de Cunha França; Maria Tereza Borges Araújo Frota; Isabela Leal Calado; Luana Lopes Padilha; Wyllyane Rayana Chaves Carvalho; Kátia Danielle Araújo Lourenço Viana; Sueli Ismael Oliveira da Conceição; Nayra Anielly Cabral Cantanhede; Sylvia do Carmo Castro Franceschini; Carolina Abreu de Carvalho (Instituto Materno Infantil de Pernambuco, 2024)
Abstract Objectives: to investigate the association of nutritional status with urinary iodine deficiency in pregnant women attending the Basic Health Units in the city of São Luís - Maranhão. Methods: cross-sectional study carried out with 261 pregnant women. Urine samples were collected for analysis of determination of urinary iodine. Iodine deficiency was considered as <150 µg/L and adequate as ≥150 µg/L. Weight and height measurements were taken at the time of collection and investigation of pre-pregnancy weight calculate BMI). Continuous variables were presented as mean, standard deviation, median, 25th and 75th percentiles, and categorical variables as simple and relative frequencies and percentages. Multivariate analyses investigate the association between pre-pregnancy and current BMI and UIC (urinary iodine concentration). Results: the mean pre-pregnancy BMI was 24.3 ± 4.5 kg/m2, and the current BMI was 27.2 ± 6.5 kg/m2. The median UIC was 181.3 µg/L (113.2-271.7), and 40.6% of the sample showed iodine deficiency. The increase in pre-pregnancy and current BMI was associated with a reduction in the prevalence of iodine deficiency in pregnant women (PR = 0.94; (CI95% = 0.88; 0.99) and PR = 0.95; (CI95% = 0.88 - 0.99), respectively). Conclusion: high BMI is positively associated with UIC and provides a reduction in iodine deficiency prevalence in pregnant women.